Genome-wide identification and characterization of the GDSL lipase gene family in Dendrobium catenatum and their potential role in drought stress tolerance and stomatal outer cuticular ledge formation - Tang, Jing; Li, Jiaying; Tang, Chunyan; Han, Xingyu; Zhang, Haiying; Yang, Beiqi; Xiao, Long; Li, Ruiying; Liu, Hangxing; Pi, Dengjin; Liu, Qinsong; Hu, Disha; et al. (Frontiers in Plant Science, 2025)
BackgroundDendrobium catenatum, a drought-resistant medicinal orchid, exhibits unique adaptations to arid environments; however, the underlying molecular mechanisms remain largely unknow. The formation of the abnormal stomatal outer cuticular ledge (OCL) is prevalent in D. catenatum and is thought to contribute to its drought tolerance. Despite this, the GDSL lipases that regulate drought resistance in D. catenatum have not yet been identified. This study aimed to systematically identify the GDSL lipase family in D. catenatum, analyze their expression patterns, screen for candidates highly expressed in the leaf epidermis and stomatal guard cells, and validate their roles through drought tolerance assays and stomatal OCL characterization.MethodsA total of 58 GDSL lipase genes were identified from the D. catenatum genome. Nine endoplasmic reticulum-localized, drought-responsive candidates were selected for functional characterization in Arabidopsis.ResultsOverexpression of D. catenatum GDSL (DcaGDSL) 25, 39, 47, and 52 in Arabidopsis decreased drought tolerance, with DcaGDSL47-overexpressing lines exhibiting accelerated water loss. Notably, DcaGDSL47, which is enriched in stomatal, reduced drought tolerance, accelerated stomatal water loss, and caused the degradation of stomatal OCL when overexpressed in Arabidopsis. These findings suggest that DcaGDSL47 plays a key role in regulating stomatal OCL formation and drought adaptation.ConclusionThis study highlights the essential roles of GDSL lipases in modulating stomatal OCL formation and drought adaptation in D. catenatum, providing a molecular basis for further investigation of drought resistance mechanisms from the perspective of stomatal OCL formation.